2022
DOI: 10.3390/jcm11185446
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs Expression Profile in Lung Inflammation: A Preliminary Study

Abstract: Background: Bronchial asthma is an inflammatory airway disease with an ever-increasing incidence. Therefore, innovative management strategies are urgently needed. MicroRNAs are small molecules that play a key role in lungs cellular functions and are involved in chronic inflammatory diseases, such as bronchial asthma. This study aims to compare microRNA serum expression between subjects with asthma, obesity, the most common co-morbidity in asthma, and healthy controls to obtain a specific expression profile spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Atopy is an exaggerated IgE-mediated immune response to foreign antigens that makes the immune system more sensitive to common allergic triggers [40]. It is a heterogeneous disease and can be related to other diseases [41][42][43][44][45][46][47][48]. Atopic disorders include various lung inflammatory diseases (e.g., allergic asthma and IgE-mediated components of allergic aspergillosis), allergic rhinitis, conjunctivitis, and atopic dermatitis, in which metabolic abnormalities of the leukotriene pathway play a crucial role [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Atopy is an exaggerated IgE-mediated immune response to foreign antigens that makes the immune system more sensitive to common allergic triggers [40]. It is a heterogeneous disease and can be related to other diseases [41][42][43][44][45][46][47][48]. Atopic disorders include various lung inflammatory diseases (e.g., allergic asthma and IgE-mediated components of allergic aspergillosis), allergic rhinitis, conjunctivitis, and atopic dermatitis, in which metabolic abnormalities of the leukotriene pathway play a crucial role [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these pathways have been reported to be closely related to NSCLC. [36][37][38][39] The 20 key signaling pathways are shown in Figure 4e.…”
Section: Go Function and Kegg Pathway Enrichment Analysismentioning
confidence: 99%
“…Despite this increased attention, the mechanistic nature remains unclear, making novel biomarkers necessary to improve NSCLC early diagnosis. In previous studies, we have reported that microRNAs (miRNAs) are correlated with several diseases [ 25 , 26 , 27 , 28 ]. MicroRNAs (miRNAs) are a family of short non-coding RNA (approximately 18–22 nucleotides) that act as post-transcriptional regulators through silencing of their downstream target mRNA [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%